A Global Silence: A Critical Interpretive Synthesis of Aboriginal Mothering Through Domestic and Family Violence. Issue 4 (November 2022) - Andrews, Shawana; Hamilton, Bridget; Humphreys, Cathy
Aboriginal women globally face extreme risk of violence and their exposure to domestic and family violence (DFV) and state sanctioned violence is increasing. Attention to the impact on Aboriginal mothering is lacking and is underpinned by issues of social justice. This study employs Critical Interpretive Synthesis to examine the evidence on Aboriginal mothering through DFV. Serrant-Green's Silences Framework was used to structure the critique, understand its problematics and generate an argument to counter the evidential silence. From 6, 117 search results, ten publications were reviewed, only four of which substantially addressed Aboriginal mothering in the context of family and domestic violence; a conspicuous absence from the literature about Aboriginal women, children, and mothering. Studies addressing Aboriginal women's experience of DFV did not credit the issue of mothering. Equally, studies that did address mothering through violence were generally not inclusive of Aboriginal women. Silence, therefore, sits at the nexus of DFV, Aboriginal women, and mothering. While violence against Aboriginal women is acknowledged as a social ill, inattention to mothering in research represents a disregard for Aboriginal women's mothering identities and roles. Aboriginal women's voice and citizenship are critical to addressing this issue.